The Debate in Academic Teaching of Political Economy and jhe Economical Pluralism in Modern France - Borisova, Margarita (Research Papers, 2017)
This study is dedicated to the contemporary debate on the teaching of political economy in France as part of a multi-dimensional process of realization of the idea for a Renaissance of political economy in Bulgaria, France and in the entire world.Based on the analysis of economic thought in France from the beginning of the 19th century until the beginning of 21st century distinguish institutional place of education systems in the teaching of political economy, as well as the role of the political economists, economists, engineers and technocrats.The main task of this study was to trace the French experience and directions of development in political economy. For this purpose we present our first study, for teaching the discipline at leading educational establishments in France and second in scientific and research centers, institutes, companies, associations, magazines and etc.We share to a large extent the concerns about the absence of pluralism and ,,control" over the economic thinking in France and expresses support for studies of the latest global trends in the development of the political economy.
Keywords: Pluralism; Debate; Political economy